The 2018 Sulawesi tsunami in Palu city as a result of several landslides and coseismic tsunamis. Issue 4 (1st October 2020) - Aránguiz, Rafael; Esteban, Miguel; Takagi, Hiroshi; Mikami, Takahito; Takabatake, Tomoyuki; Gómez, Matías; González, Juan; Shibayama, Tomoya; Okuwaki, Ryo; Yagi, Yuji; Shimizu, Kousuke; Achiari, Hendra; et al.
ABSTRACT: The September 28 2018 Palu tsunami surprised the scientific community, as neither the earthquake magnitude nor its strike-slip mechanism were deemed capable of producing the wave heights that were observed. However, recent research has shown that the earthquake generated several landslides inside Palu bay. The authors conducted a post-disaster field survey of the area affected to collect spatial data on tsunami inundation heights, nearshore and bay bathymetry, and carried out eyewitness interviews to collect testimonies of the event. In addition, numerical simulations of the tsunami generation and propagation mechanisms were carried out and validated with the inferred time series. Seven small submarine landslides were identified along the western shore of the bay, and one large one was reported on the eastern shore of Palu City. Most of these landslides occurred at river mouths and reclamation areas, where soft submarine sediments had accumulated. The numerical simulations support a scenario in which the tsunami waves that arrived at Palu city 4–10 min after the earthquake were caused by the co-seismic seafloor deformation, possibly coupled with secondary waves generated from several submarine landslides. These findings suggest that more comprehensive methodologies and tools need to be used when assessing probabilistic tsunami hazards in narrow bays.